2018
DOI: 10.1123/pes.2017-0060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Soccer Game on Cardiac Biomarkers in Adolescent Players

Abstract: This is the first study to investigate the acute responses of cardiac biomarkers to a soccer game in adolescent male players. The postgame elevation of cardiac biomarkers and their rapid recovery are indicative of a physiological rather than a pathological response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
2
15
1
Order By: Relevance
“…To the best of our knowledge, no study has investigated cardiac troponins in RS participants. However, although the findings of the present study are in accordance with the results obtained by Hosseini et al, (13) in adolescent soccer players and in studies conducted on other intermittent sports (24), the increase in troponin level was much higher in our young participants. The greater elevation in troponins may be explained by the higher absolute HR response (185.4 bpm) of our young players as compared with reference HR values observed during soccer matches (generally 165-175 bpm) (23).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To the best of our knowledge, no study has investigated cardiac troponins in RS participants. However, although the findings of the present study are in accordance with the results obtained by Hosseini et al, (13) in adolescent soccer players and in studies conducted on other intermittent sports (24), the increase in troponin level was much higher in our young participants. The greater elevation in troponins may be explained by the higher absolute HR response (185.4 bpm) of our young players as compared with reference HR values observed during soccer matches (generally 165-175 bpm) (23).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a recent study using cardiac magnetic resonance imaging with late gadolinium enhancement also indicated that, even though cardiac troponins and N-terminal pro-brain natriuretic peptide levels are high after endurance events, there is no evidence of any detectable myocardial damage or acute changes in left or right ventricular function (29). Additionally, similar to our participants, a previous study reported no unusual cardiovascular symptoms during or following exercise despite an increase in troponin levels (13). Finally, elite marathon runners have comparatively lower troponin levels than their non-elite counterparts after a race, which may occur in conjunction with improved resistance against exercise-induced cardiomyo-cyte membrane damage (5).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The search process appears outlined in Figure 1. Fourteen studies met the inclusion/exclusion criteria that included 21 groups covering a total sample of 336 9 participants (72 females) who had a mean age of 15.1 ± 2.3 years (12,13,49,(76)(77)(78)20,27,30,38,39,(46)(47)(48). Two studies provided complete data from more than one subgroups contributing with different estimates by sex (27,78) or Tanner stage (30), which were treated as different units for the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…One study provided four outcome measurements from the same group at different exposures (12), which were controlled for multiplicity within the models (51,81). Interventions were based on five different modalities: in nine studies participants ran [three treadmill protocols (45 to 90 min) (13,46,77), five half marathons (12,27,47,48,76) and one full marathon (78)], in two studies basketball was employed (38,49), in one a soccer match (20), in one study participants swam for 60 min (30) and one included a set of table tennis exercises (39). Table 1…”
Section: Resultsmentioning
confidence: 99%